Core Project Teams as an Organizational Approach for Projects and their Management - Kähkönen, Kalle; Keinänen, Marko; Naaranoja, Marja (Elsevier, 2013)
Traditional options for organizing projects are well known covering solutions from pure project organizations up to functional organizations via variations of matrix organizations. Besides of these alternatives capable and clever project management professionals are continuously establishing informal structures and linkages to facilitate necessary cooperation between people and project partners. Particularly modern projects with their turbulent and dynamic nature have apparent needs that are beyond the solutions provided by traditional options. This paper shall build around the concept “core team”. We have recognized the appearance and significance of core teams in case projects the introduction of which shall form an important part of the paper. The named case projects are mainly from the building construction sector being the main focus area of the authors. Regarding this type of projects the project core team approach can be very helpful in bringing key partners more closely together. Examples of such partners are contractors, designers and clients. It seems that a core project team can play a very important role regarding efficient decision making and communication. However, the role and mandate of core teams is still rather vague in the project management discipline.
Keywords: Co-design; Co-development; organization; Partnering; projects; teams; project management; fi=Tuotantotalous|en=Industrial Management|